Protein design of two-component tubular assemblies similar to cytoskeletons - Masahiro Noji; Yukihiko Sugita; Yosuke Yamazaki; Makito Miyazaki; Yuta Suzuki (Nature Communications)
Abstract Recent advances in protein design have ushered in an era of constructing intricate higher-order structures. Nonetheless, orchestrating the assembly of diverse protein units into cohesive artificial structures akin to biological assembly systems, especially in tubular forms, remains elusive. To this end, we develop a methodology inspired by nature, which utilises two distinct protein units to create unique tubular structures under carefully designed conditions. These structures demonstrate dynamic flexibility similar to that of actin filaments, with cryo electron microscopy revealing diverse morphologies, like microtubules. By mimicking actin filaments, helical conformations are incorporated into tubular assemblies, thereby enriching their structural diversity. Notably, these assemblies can be reversibly disassembled and reassembled in response to environmental stimuli, including changes in salt concentration and temperature, mirroring the dynamic behaviour of natural systems. This methodology combines rational protein design with biophysical insights, leading to the creation of biomimetic, adaptable, and reversible higher-order assemblies. This approach deepens our understanding of protein assembly design and complex biological structures. Concurrently, it broadens the horizons of synthetic biology and material science, holding significant implications for unravelling life’s fundamental processes and enabling future applications.